Research of metastable conditions and heat - mass transfer processes in magnesium chloride solutions - Bazanov, A.V.; Padohin, V.A. (Ye.A.Buketov Karaganda State University Publishing house, 2010)
In the given work results of an experimental research of pulsations of temperature on the evaporating surface and in the steam volume of the laboratory evaporator installation are given. Research of the major factors influencing pulsations of temperature in the solution, on the phase boundary and in the steam-gaseous medium is carried out.
Keywords: pulsations of temperature; magnesium chloride solutions; heat - mass transfer; kvazi-elastic periodic force